Performance of Broilers Supplemented With Peppermint ( L.) Powder - Nematollah Asadi PhD; Seyed Davood Husseini PhD; Mohammad-Taghi Tohidian PhD; Nargess Abdali PhD; Amir Mimandipoure PhD; Mahmoud Rafieian-Kopaei PhD; Mahmoud Bahmani PhD (SAGE Publishing, 2017)
This study was conducted to determine the effects of dietary supplementation of peppermint ( Mentha piperita L.) on the performance of broiler chicks. 500 Ross broiler chicks were divided into 5 treatment groups of 4 replications in a completely randomized design format. The diets were ISO-caloric and ISO-nitrogenous ones and contained 1.5, 3, 4.5, and 6 g/kg of peppermint powder. At start, growing, and end periods, the effects of peppermint powder on average daily weight gain, feed conversation ratio, and mortality rate were studied. The results of the present study showed that over a production period of 42 days peppermint had a significant effect on average daily weight gain and feed conversation ratio when compared with the control group ( P < .05). The level of 4.5 g/kg had the highest average daily weight gain (52.78 g), and control treatment with 46.98 g had the least average daily weight gain among different levels of peppermint. The level of 4.5 g/kg and 6 g/kg of peppermint had the least mortality compared to control treatment during training period ( P < .05). From this experiment, we can conclude that treatment with 4.5 g/kg peppermint powder has better performance and carcass characteristics in broilers.